2014
DOI: 10.1111/jfs.12162
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Various Essential Oils against Pathogens and Spoilage Microorganisms in Fresh Produce

Abstract: This study was conducted to investigate the antibacterial effect of various essential oils (EOs) against pathogens and fresh produce spoilage bacteria using the agar disc diffusion method and 96‐well dilution method. Moreover, the antibacterial effect of EOs to reduce the level of total mesophilic microorganisms in fresh leaf lettuce and radish sprouts was determined by dipping method. Furthermore, membrane damage of two pathogens before and after treatment with effective EOs was determined using the fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Our results of the antimicrobial assay of Algerian thyme essential oils corroborated earlier studies that described the powerful antimicrobial effects of T. vulgaris oil (20). The reported inhibition zone diameters for E. coli ATCC 25922, P. aeruginosa ATCC 27853 and C. albicans ATCC 10231 were 30.67 mm, 14 mm and 25.74 mm, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results of the antimicrobial assay of Algerian thyme essential oils corroborated earlier studies that described the powerful antimicrobial effects of T. vulgaris oil (20). The reported inhibition zone diameters for E. coli ATCC 25922, P. aeruginosa ATCC 27853 and C. albicans ATCC 10231 were 30.67 mm, 14 mm and 25.74 mm, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…They are highly similar to ours regarding the two bacteria, but yeast turned out to be much less sensitive. Another study (20) showed a halo diameter as large as that obtained for our EOs for B. cereus ATCC 10876 (> 45 mm). Furthermore, the susceptibility of Proteus sp.…”
Section: Discussionsupporting
confidence: 53%
“…The ethanol and hexane extracts were reconstituted in 0.05% of Tween 80 separately, and this was with slight modifications to the method employed by Hyun et al (2015). The sliced cuts of Citrullus lanatus were dipped into the solution for 10 minutes and later transferred and packaged in nylon films.…”
Section: Application Of the Extracts To Fresh Cuts Of Citrullus Lanatusmentioning
confidence: 99%
“…Vegetables are an important part of a balanced and healthy diet (Mediterranean diet) and minimally processed foods such as ready-to-eat salads have become more and more popular because they are a healthy, nutritional, and convenient choice among consumers (Olaimat & Holley, 2012;Vandekinderen et al, 2008). Among minimally processed vegetables, shredded carrots are particularly popular; however, they are perishable products and can be contaminated throughout the food chain Hyun, Bae, Song, Yoon, & Lee, 2015). Besides ensuring shredded carrots shelf-life extension, there is also a growing interest of researchers and consumers to keep and enhance produce's bioactive composition, which is mostly arise from the presence of antioxidants, especially phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The EOs and plant extracts are derived from various plant materials as leaves, flowers, fruits, roots, shoots, and seeds (Burt, 2004). The biocidal activity of EOs and plant extracts is well known, however, the way of application and concentration levels needed to be examined for each commodity (Chrysargyris et al, 2017;Hyun, Bae, Song, et al, 2015;Stavropoulou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%